The Laschamp geomagnetic excursion featured in nitrate record from EPICA-Dome C ice core - Traversi, R. (Sci Rep, 2016)
Here we present the first direct comparison of cosmogenic (10)Be and chemical species in the period of 38–45.5 kyr BP spanning the Laschamp geomagnetic excursion from the EPICA-Dome C ice core. A principal component analysis (PCA) allowed to group different components as a function of the main sources, transport and deposition processes affecting the atmospheric aerosol at Dome C. Moreover, a wavelet analysis highlighted the high coherence and in-phase relationship between (10)Be and nitrate at this time. The evident preferential association of (10)Be with nitrate rather than with other chemical species was ascribed to the presence of a distinct source, here labelled as “cosmogenic”. Both the PCA and wavelet analyses ruled out a significant role of calcium in driving the (10)Be and nitrate relationship, which is particularly relevant for a plateau site such as Dome C, especially in the glacial period during which the Laschamp excursion took place. The evidence that the nitrate record from the EDC ice core is able to capture the Laschamp event hints toward the possibility of using this marker for studying galactic cosmic ray flux variations and thus also major geomagnetic field excursions at pluri-centennial-millennial time scales, thus opening up new perspectives in paleoclimatic studies.